A very small novel patch antenna design for WLAN application - Muhammad Solihin, Zulkifli; Mohd. Fareq, Abd. Malek, Dr.; Mohd Faizal, Jamlos, Dr.; Khairudi, Mohd Juni; Mohd Shaharom, Idris; Mohd Iskandar, Mohd Saleh; Mohd Hafizuddin, Mat; Ronald, Suzanna Harun (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/